2020
DOI: 10.1183/16000617.0038-2020
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory viral sepsis: epidemiology, pathophysiology, diagnosis and treatment

Abstract: According to the Third International Consensus Definition for Sepsis and Septic Shock, sepsis is a life-threatening organ dysfunction resulting from dysregulated host responses to infection. Epidemiological data about sepsis from the 2017 Global Burden of Diseases, Injuries and Risk Factor Study showed that the global burden of sepsis was greater than previously estimated. Bacteria have been shown to be the predominant pathogen of sepsis among patients with pathogens detected, while sepsis caused by viruses is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 141 publications
1
36
0
5
Order By: Relevance
“…The initial presentation of sepsis secondary to viral pneumonia may be based on new-onset or worsening hypotension, altered mental status and other signs of organ dysfunction, such as renal dysfunction, liver dysfunction, or thrombocytopenia and should be differentiated by bacterial superinfection. Sometimes, ageing patients, immunocompromised patients, or those living with chronic obstructive pulmonary disease can have a less specific presentation with rapidly worsening clinical conditions [20]. In some cases, the activation of the inflammatory response caused by a viral infection can trigger a pro-coagulative status thereby increasing the risk of cerebrovascular events in apparently low-risk patients [21].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…The initial presentation of sepsis secondary to viral pneumonia may be based on new-onset or worsening hypotension, altered mental status and other signs of organ dysfunction, such as renal dysfunction, liver dysfunction, or thrombocytopenia and should be differentiated by bacterial superinfection. Sometimes, ageing patients, immunocompromised patients, or those living with chronic obstructive pulmonary disease can have a less specific presentation with rapidly worsening clinical conditions [20]. In some cases, the activation of the inflammatory response caused by a viral infection can trigger a pro-coagulative status thereby increasing the risk of cerebrovascular events in apparently low-risk patients [21].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…It is very difficult to distinguish between viral sepsis and bacterial sepsis. Recent studies have found that the distinct of viral and bacterial sepsis can only be distinguished by a complex method of whole blood genomics [ 54 ]. The therapy of sepsis is mainly combining the supportive therapy with the interventions aimed at the root causes of pathogens.…”
Section: The Correlation Between Covid-19 and Sepsismentioning
confidence: 99%
“…As Infecções virais graves podem causar síndromes sépticas, isso geralmente ocorre por meio do knockdown viral da resposta antiviral inicial, entretanto, vários vírus, como o Parechovírus, também podem causar síndromes e complicações inflamatórias semelhantes à sepse. (GU et al, 2020). Os estudos de Gupta et al (2018); Gu et al (2020) e Silva et al (2021), revelam que a sepse viral tende a provocar infecção no trato respiratório e na corrente sanguínea.…”
Section: Metodologiaunclassified
“…(GU et al, 2020). Os estudos de Gupta et al (2018); Gu et al (2020) e Silva et al (2021), revelam que a sepse viral tende a provocar infecção no trato respiratório e na corrente sanguínea. Além disso, os estudos apontam a Influenza A, o…”
Section: Metodologiaunclassified